The Representation of Sarcasm in “How I Met Your Mother Season 2”: A Pragmatics Study - Hafsyah Husin Siagian; ANNA RIANA SURYANTI TAMBUNAN; Morada Tetty (Universitas Negeri Medan, 2019)
The aims of this study were to investigate the maxims flouted by the major characters, the realization of sarcasm based on the scene, and the reasons for sarcastic utterances found in “How I Met Your Mother Season 2” using a pragmatics study. The study was conducted using a textual research. The data of this study were taken from the transcripts of “How I Met Your Mother Season 2”. The data of this study were the sarcastic utterances that appeared in “How I Met Your Mother Season 2”. The data analysis was taken by coding and developing theme from the data based on the theory proposed by Braun and Clarke. The findings indicated that all four maxims were flouted by the major characters in “How I Met Your Mother Season 2”. In addition, there were several sarcastic utterances in which the characters flouted more than one maxim. Based on the research results, the most frequently flouted maxim was the maxim of quality. It could be seen that the situations in which sarcasm appeared in “How I Met Your Mother Season 2” mostly occurred at night. Then, it was also found that all purposes of sarcasm were present in the sarcastic utterances. There were even several sarcastic utterances which served more than one purpose. Sarcasm which served as an evaluation was most frequently used by the characters in order to hide the negative effects of their criticism and also to create the positive effects of their sarcastic praise towards their interlocutors